Design Of A Linear DC Motor For High Thrust Constants Characteristics - Fairul Azhar, Abdul Shukor; Raja Nor Firdaus Kashfi, Raja Othman; Mohd Luqman, Mohd Jamil (Asian Research Publishing Network (ARPN), 2016)
Traditionally a linear motion system consists of a rotational motor and motion translation component. However, the traditional systems inherit several drawbacks that contribute into operational limitation. Currently, use of a linear motor is seen as an alternative to produce direct linear motion without use any motion translation. Linear DC Motor (LDM) is one type of linear motor. Previously, a LDM has been developed to be use in a linear displacement system. Based on experimental result, it could achieve a desired displacement with fast settling time and low overshoot. However, in order to improve the system performance especially in term of time response, a new LDM need to be designed. In this paper, a LDM for similar application was designed. The shape of the LDM has been change from a rectangular to quarter circle due to changes in shape of permanent magnet. Furthermore, material of the permanent magnet also has been changed from ferrite to NdFeB to increase the magnetic flux density in air gap. Based on the designed, the LDM has produce about 3.1 N/A and 35.12 ms in term of thrust constant, kf and mechanical time constant, Tm respectively. In comparison with previous LDM, it only produced about 1.6 N/A and 111.72 ms in term of thrust constant, kf and mechanical time constant, Tm respectively.